2002
DOI: 10.1002/ajmg.10978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular etiology of gut malformations and diseases

Abstract: This review describes recent advances using animal models in the analysis of the molecular controls of gastrointestinal development, with specific attention to mutations causing maldevelopment similar to those seen in human gut malformations. By focusing on specific human gut pathologic conditions and maldevelopment, we describe the probable roles of signaling pathways, including the hedgehog pathway, the bone morphogenic protein pathway, and the role of the homeotic genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 108 publications
1
35
0
Order By: Relevance
“…Thus, we cannot exclude the possibility that Jag1 staining at the basal membrane of crypt cells is of mesenchymal origin. This assumption reinforces the model in which complex cellcell, including epithelial-mesenchymal, interactions play a pivotal role in gut development and homeostasis (reviewed by Kedinger et al, 1998;De Santa Barbara et al, 2002;Faure and de Santa Barbara, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, we cannot exclude the possibility that Jag1 staining at the basal membrane of crypt cells is of mesenchymal origin. This assumption reinforces the model in which complex cellcell, including epithelial-mesenchymal, interactions play a pivotal role in gut development and homeostasis (reviewed by Kedinger et al, 1998;De Santa Barbara et al, 2002;Faure and de Santa Barbara, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Hh ligands (Shh and Ihh), which are expressed in the epithelium from early developmental stages, signal in a paracrine fashion to the mesenchyme (Kolterud et al, 2009;Ramalho-Santos et al, 2000). Loss of both Hh ligands or deletion of the major Hh signal transducer, smoothened (Smo), severely reduces mesenchymal proliferation and results in a digestive tract that is 90% shorter than controls -even shorter than the Wnt5a −/− gut (de Santa Barbara et al, 2002;Mao et al, 2010). Similarly, inactivating Notch signaling by deletion of the Notch effector Rbpj only in the mesenchyme diminishes the number of subepithelial fibroblasts and results in intestines that are 20-30% shorter than controls .…”
Section: Ror2mentioning
confidence: 99%
“…In addition, the splanchnic mesoderm-derived mesenchyme that underlies the gut is organized along a radial axis of symmetry into distinct cell layers establishing oriented smooth muscle bands that control local movement of the gut tube. Organogenesis and tissue homeostasis within the digestive tract require continuous interaction between endodermal epithelium and subjacent mesenchyme (Haffen et al, 1987;Kedinger et al, 1998), and disruption of these interactions is implicated in human gastrointestinal (GI) birth defects and cancers (Bhowmick et al, 2004;de Santa Barbara et al, 2002;Yauch et al, 2008). Despite their importance, the molecular mediators of epithelial-mesenchymal interchange are poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In a chicken GI explant culture, Shh was shown to regulate mesenchymal patterning and inhibit smooth muscle differentiation (Sukegawa et al, 2000). Proliferation of intestinal intervillus epithelium is reduced in Ihh -/-mice (Ramalho-Santos et al, 2000), whereas Shh -/-mice show multiple gut anomalies, including tracheo-esophageal fistula and anorectal atresia (Litingtung et al, 1998;Ramalho-Santos et al, 2000), among the common congenital GI anomalies observed in humans with mutations in Hh pathway genes (Arsic et al, 2002;de Santa Barbara et al, 2002;Kang et al, 1997;Kim et al, 2001;Nanni et al, 1999). However, the modest phenotypes of individual Shh or Ihh mutants and the extensive overlap in their expression domains are indicative of a potential redundancy in their actions, a conclusion supported by the enhancing action of reducing gene dosage in a background sensitized by the loss of one these proteins (RamalhoSantos et al, 2000).…”
Section: Introductionmentioning
confidence: 99%